Racism as a Social Issue in Black Eyed Peas Song “Where is the Love?” - Sutrisno, Bejo; Tantriana, Yulan Dewi; Rachmawati, Budi (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
This research departs from the problems that occur related to racial discrimination that occurred in America. This study aims to examine the social issue surrounding the superiority of racist violence. Finding out the types of racism exist and describing how it is portrayed in the Black Eyed Peas song “Where is The Love?” are the goals of this study. Content analysis is a type of qualitative research that was employed in this research by the researcher. Unit analysis was used to gather data from the song through words and lyrics. The themes in the data were categorized, coded, and classified. Following that, the data were interpreted using the writer's point of view. The result showed that “Where is The Love?” song contained racism in the form of prejudice, and physical violence occur in the song. The “Where is The Love?” song represents racism in America because it was based on the tragedy happened in the past where Black Americans have been treated bad by the superiority.